Earthquake Disaster Mitigation To Improve Community Preparedness In Betungan Village - Kurniawan, Dwiki; Andika, Ryndry; Zahesya, Favien Riza; Putra, Redo Osi; Febriansyah, Angga Trio; Fredricka, Jhoanne; Sartika, Devi; Elfianty, Lena (Jurnal Inovasi Kerja Nyata, 2025)
Indonesia is a country prone to natural disasters, especially earthquakes, due to its location at the meeting point of three major tectonic plates. The lack of education and awareness among the public regarding disaster risks often exacerbates the impact of such events. This Devotion aims to enhance public understanding and preparedness for earthquakes through poster-based disaster mitigation awareness campaigns. The activities were conducted in Betungan Village, Selebar Subdistrict, Bengkulu City, using a qualitative approach. The three stages of the activity included the development of disaster management documents, community organisation, and direct outreach in the field. The results showed an increase in public awareness and knowledge of evacuation and disaster mitigation measures. Despite some technical and social challenges, the activity successfully fostered active community participation and served as an effective model for disaster education at the community level.